Understanding variant selection and texture in additively manufactured red-gold alloys. (1st April 2022) - Ghasemi-Tabasi, Hossein; Larcher, Margaux N.D.; Cayron, Cyril; Jhabvala, Jamasp; Van Petegem, Steven; Kalentics, Nikola; Boillat, Eric; Logé, Roland E.
Abstract: Printing gold alloys parts is a challenge due to the high reflectivity and thermal conductivity of these materials. Recent studies show an improvement in printing gold using the Laser Powder Bed Fusion (L-PBF) process; however, the impact of the A1→L10 phase transformation on printed red-gold alloy has not been studied. In this work, 3D printed red-gold samples with different post-processing conditions have been heat-treated at 250 °C to investigate the effect of the sample stress states on variant selection, by Electron Backscatter Diffraction. Synchrotron X-ray diffraction experiments reveal the presence of a non-negligible amount of tetragonal phase in the as-build red-gold samples. The use of an intermediate heat treatment at 600 °C to eliminate small domains of tetragonal phase formed during the manufacturing process demonstrates that the crystallographic textures following heat treatment are highly dependent on the stress-state during the early stage of the phase transformation. Graphical abstract: Image, graphical abstract